PENGALAMAN USAHA DARI PEMBELAJARAN ESKALASI KOMITMEN - Nurchayati Nurchayati; Parju Parju (Serat Acitya, 2019)
This study examines the causality relationship between experience and escalation of commitment to prestige milkfish SMEs in Semarang, Central Java, Indomesia. This study used a laboratory experimental design with subjects of 60 SMEs. The independent variable is experience measured by the length of effort of the average business of 11 years and the dependent variable is the escalation of commitment as measured by investment decisions on a scale of 10 to 100.The results of the study with both descriptive and independent t-test analysis showed that experienced SMEs had a greater escalation of commitment compared to SMEs who lacked experience. This research is expected to provide empirical evidence that supports that business actors' experience influences decision making and provides a better understanding of the factors of experience that lead to escalation of commitment.keywords: experience, escalation of commitment, SMEs